2011
DOI: 10.1503/jpn.090100
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive microstructural abnormalities in autism: a DTI study

Abstract: Background: Recent studies have reported abnormal functional connectivity patterns in the brains of people with autism that may be accompanied by decreases in white matter integrity. Since autism is a developmental disorder, we aim to investigate the nature and location of decreases in white and grey matter integrity in an adolescent sample while accounting for age. Methods: We used structural (T 1 ) imaging to study brain volumetrics and diffusion tensor imaging (DTI) to investigate white and grey matter inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
87
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 43 publications
7
87
1
Order By: Relevance
“…However, only a few diffusion imaging studies of autism even mention possible differences in head motion, let alone measure it. Only two papers report any quantitative analysis of the amount of motion present in the DWI scans, or report what motion threshold was used for excluding participants (9,10). Ten studies gathered imaging data while some participants were under general anesthesia and an additional two while participants were sleeping naturally, presumably reducing head motion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only a few diffusion imaging studies of autism even mention possible differences in head motion, let alone measure it. Only two papers report any quantitative analysis of the amount of motion present in the DWI scans, or report what motion threshold was used for excluding participants (9,10). Ten studies gathered imaging data while some participants were under general anesthesia and an additional two while participants were sleeping naturally, presumably reducing head motion.…”
Section: Discussionmentioning
confidence: 99%
“…Another potential problem that few diffusion studies of autism address or even mention is data quality. Indeed, to our knowledge, only two studies (9,10) report quantitative analyses of the amount of motion in their DWI data. Group differences in head motion could be a serious confounding factor, given that head motion is likely to be greater in children with autism, and group differences in head motion can lead artifactually to just the effects most often reported: reduced FA in white matter tracts in ASD (11).…”
mentioning
confidence: 99%
“…First, volumetric changes can evolve over an extended time (Sidaros et al, 2009;Trivedi et al, 2007;Wu et al, 2010a) and may be evident later than changes seen on other advanced imaging techniques such as DTI (Bendlin et al, 2008;Groen et al, 2010;Hutchinson et al, 2010;Wu et al, 2010a). It should be kept in mind that the relation between tissue integrity, as measured by volumetry, and outcome may be dynamic and complex, particularly in the earlier phases of recovery, as trajectories of rapid cognitive recovery and incomplete degenerative tissue change may be progressing in opposing directions and to differing degrees.…”
Section: Mrimentioning
confidence: 99%
“…One study reported areas of reduced FA in children with high functioning autism (mean age 12.8 years) compared to controls, within the frontal WM and the superior longitudinal fasciculus, and increased FA within peripheral WM (Sahyoun et al, 2010). Three studies did not find any significant differences in FA values (Groen et al, 2011;Fletcher et al, 2010;Thomas et al, 2010). And finally, studies conducted only in subjects with autism (subgroup, not the entire spectrum) reported reductions in FA in the frontal, parietal and temporal lobes (BarneaGoraly et al, 2010); the frontal lobe (Mengotti et al, 2011;Pardini et al, 2009); and CC (Mengotti et al, 2011).…”
Section: Dti Findings In Autism: Review Of Published Articlesmentioning
confidence: 98%